Long‐term survival of head and neck squamous cell carcinoma after bone marrow transplant. Issue 11 (21st August 2020) - Douglas, Catriona M.; Jethwa, Ashock R.; Hasan, Wael; Liu, Amy; Gilbert, Ralph; Goldstein, David; De Almedia, John; Lipton, Jeff; Irish, Jonathan C.
Abstract: Purpose: The risk of developing head and neck squamous cell carcinoma (HNSCC) in patients with graft versus host disease (GVHD) after bone marrow transplant (BMT) is well established but large series reporting outcomes are sparse. Methods: Retrospective, single institution, study of patients with GVHD and HNSCC after BMT, between January 1, 1968, and June 30, 2016. Results: In total, 25 patients were studied, of which 21 (84%) were male and 4 (16%) were female. Mean age for BMT was 41 (18‐65) years. All patients developed GVHD, most common site was oral cavity (19 patients, 76%). Mean age for diagnosis of HNSCC was 52 (28‐76) years. Mean time between BMT and diagnosis of HNSCC was 12 (2‐13) years. The 2‐year progression‐free survival (PFS) was 61.4%, 5‐year PFS was 56.7%. The 2‐year overall survival (OS) was 82.8%, 5‐year OS was 68.7%. Conclusion: HNSCC can develop many years after BMT in patients without the classic risk factors for head and neck cancer. The majority were seen with oral cancer and with early‐stage disease likely due to active surveillance and early detection in this patient population.